Determination Heavy Metal Levels of Some Feed Ingredients Produced in Tekirdag, Turkey - KOC, FISUN; TUFAN, MAHMUT; KEMAL GURCAN, E.; GENC, SERDAR (Asian Journal of Chemistry, 2010)
Main objective of this study is to determine the pollution levels and province variatons of polluting agents in some feed ingredients produced in Tekirdag and also to determine whether legal tolerance levels had been exceed or not. In order to achive this goal, cadmium, lead, arsenic, copper, zinc, iron analysis were performed during the fiscal year of 2007 from feed ingredients (wheat, sunflower, barley) in two province Tekirdag. Atomic absorption spectrophotometer (AAS) had been utilized for heavy metals. The data showed heavy metal level in feed ingredients for ruminants in Tekirdag were lower compared to current European regulations. The monitoring of these elements content is necessary as well, although not at same level as, for instance for lead and cadmium.